2013
DOI: 10.1038/nature12441
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanism of MEK inhibition determines efficacy in mutant KRAS- versus BRAF-driven cancers

Abstract: KRAS and BRAF activating mutations drive tumorigenesis through constitutive activation of the MAPK pathway. As these tumours represent an area of high unmet medical need, multiple allosteric MEK inhibitors, which inhibit MAPK signalling in both genotypes, are being tested in clinical trials. Impressive single-agent activity in BRAF-mutant melanoma has been observed; however, efficacy has been far less robust in KRAS-mutant disease. Here we show that, owing to distinct mechanisms regulating MEK activation in KR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
270
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(292 citation statements)
references
References 29 publications
21
270
0
1
Order By: Relevance
“…Existing MEK inhibitors lack specificity against oncogenic KRAS versus BRAF mutations that converge on the MAPK signaling pathway. We studied the novel MEK inhibitor GDC-0623, which has been shown to have superior efficacy against KRAS compared with BRAF mutant tumors (10). We found that GDC-0623 treatment can potently up-regulate BIM and to a greater extent than observed for other MEK inhibitors that have undergone clinical evaluation (32,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing MEK inhibitors lack specificity against oncogenic KRAS versus BRAF mutations that converge on the MAPK signaling pathway. We studied the novel MEK inhibitor GDC-0623, which has been shown to have superior efficacy against KRAS compared with BRAF mutant tumors (10). We found that GDC-0623 treatment can potently up-regulate BIM and to a greater extent than observed for other MEK inhibitors that have undergone clinical evaluation (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to BRAF mutant melanomas, this limited efficacy indicates that different mechanisms of inhibition are required for optimal antitumor activity in each genotype. Structural and functional analyses indicate that the novel MEK inhibitor GDC-0623 can achieve superior efficacy in KRAS-driven tumors by forming a strong hydrogen bond interaction with Ser 212 in MEK that is critical for blocking MEK feedback phosphorylation by wildtype RAF (10). On the basis of favorable preclinical data, GDC-0623 is currently being studied in a phase I clinical trial.…”
mentioning
confidence: 99%
“…Unfortunately, despite the long available knowledge about mutant KRAS, no successful therapeutic approaches have entered clinical practice. One targetable molecule MEK might help to block signaling downstream of mutated RAS and several inhibitors of MEK are currently in clinical trials (6,7,37). Only recently, a new MEK inhibitory substance was reported to rescue cetuximab resistance in KRAS-mutated colorectal cancer cell lines (38).…”
Section: Discussionmentioning
confidence: 99%
“…These include MEK, PI3K, and AKT inhibitors. Most of these drugs are still in early clinical trials (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Another phenomenon is priming, which can lead to activation via kinase inhibitors, which has been observed for several kinases like AKT, MEK, and JAK (Okuzumi et al, 2009;Andraos et al, 2012;Hatzivassiliou et al, 2013). Priming describes the up-regulation of the phosphorylated form of the targeted kinase upon inhibition, which can lead to an activation of the pathway once the inhibitor is removed.…”
Section: Downloaded Frommentioning
confidence: 99%